Students' Perceptions and Experiences of Using Memrise For Learning English Vocabulary: A Mixed-Methods Study - Hairani, Rosyidah Nur; Melani, Boniesta Zulandha; Lail, Husnul (LITPAM, 2026)
This study examines students' perceptions and experiences regarding the use of the Memrise application for English vocabulary learning within the English Education Department at the University of Mataram, utilizing the Technology Acceptance Model (TAM) as a theoretical framework. A mixed-methods design was employed, combining a descriptive quantitative approach with qualitative interviews. Questionnaire data were collected from 38 second-year students who had used Memrise for at least three months, while semi-structured interviews were conducted with 10 selected students to gain deeper insight into their experiences. Quantitative data were analyzed using descriptive statistics, whereas qualitative data were analyzed using the Miles and Huberman interactive model. The findings indicate that students held positive perceptions regarding Memrise's usefulness (mean scores of 3.58–3.95) and ease of use (mean scores of 3.58–4.05). Key benefits identified included vocabulary retention through repetition, pronunciation practice, and learning flexibility. However, students also encountered challenges, such as internet connectivity issues (mean score of 3.53), limitations regarding premium features, and a scarcity of advanced-level vocabulary materials. The study concludes that Memrise is perceived positively as a supportive and flexible vocabulary learning tool, although improvements in accessibility and content variety are needed. This research contributes to the literature on technology-based vocabulary learning and the application of TAM within the context of Indonesian higher education.